Ahoy! - Blackall, Sophie (New York Anne Schwartz Books, 2024)
Join a child captain and parent first mate as they embark on a wild high seas adventure-all without leaving the living room! This imaginative romp of a picture book is filled with glorious illustrations from a beloved Caldecott Medalist and New York Times bestselling creator.
Raise the mainsail! Batten the hatches! It's time to set sail...on the couch! There's a storm coming, and a child is ready to captain the ship. "Make haste and climb aboard," they call out to their parent, "before you're swept out to sea!" Sea? What sea? The parent is only trying to vacuum the rug. But the child is adamant. It's not a rug--it's the ocean. And that broom? It's the ship's mast. Soon enough, child and parent are both off on an imaginary nautical adventure! Here is a thoroughly engaging, hilarious picture book that celebrates the joys of playing make-believe--and hanging out with a parent!
Ages 4-8.
113580
Keywords: Sailing -- Juvenile fiction; Pirates -- Juvenile fiction; Imagination -- Juvenile fiction; Parent and child -- Juvenile fiction; Play -- Juvenile fiction; House cleaning -- Juvenile fiction; Adventure stories; Adventure and adventurers -- Fiction; Action and adventure fiction; Picture books